The Effectiveness of Business Intelligence Management Implementation in Industry 4.0 - Choi, Lee Kyung; Panjaitan, Aropria Saulina; Apriliasari, Dwi (Pandawan Sejahtera Indonesia, 2022)
Changes in business processes that run very fast in the industrial era 4.0 have positive and negative impacts on business players. Industry 4.0 is a technology that companies need to promote Industry 4.0 is a technology that businesses need to promote innovation strategies and respond quickly in a volatile market. It primarily focuses on interconnectivity, digital technology, predictive analytics, and machine learning to transform the way businesses operate and thrive. As a result, this article suggests and encourages the implementation of Industry 4.0 in organizations. Examining the current state of business intelligence (BI), how it is positively impacting organizations at the economic and business levels in terms of decision making, and some success stories applied across various business, academic, social, and government circles. Furthermore, it discusses the expected future of Industry 4.0, particularly in BI, and how businesses should prepare for this revolution. This article contributes knowledge about the current state and positive consequences of Industry 4.0, as well as the rapid advancement of technology when implemented in organizations and the harmonization of production and intelligent digital technology.